Trails in Academic and Administrative Leadership in Kenya - Michieka, R. W. (Codesria book series., 2017)
Scholars, especially those interested in understanding how leadership has inhibited academic freedom and hindered effectiveness of institutions of higher learning have for long been engaged by the very important manner in which governance and leadership of higher education institutions in Africa is constituted and managed. The fact that there has been a dearth of work based on the experiences of those who have served as university leaders has created a major gap. Questions remain on how leaders of higher education institutions are identified, how they are prepared, the personal predispositions that individuals bring to the exercise of such positions and their personal experiences regarding what energizes or inhibits the performance of their work. Until recently, presidents in most African countries served as chancellors of public universities, identification of those who served as university leaders was largely a political process. But much has changed, with most countries establishing oversight bodies and the overall governance of higher education institutions divorced from the day-to-day political processes. Trails in Academic and Administrative Leadership in Kenya provides a personal account of the experiences in higher education leadership from an individual whose tenure in leadership straddled the two eras. In this book, Prof. Michieka provides an account of how his early education prepared him for roles in academic and institutional leadership in Kenya. The author shares his experiences on the trails he had to navigate as an academic, a vice-chancellor and a chairperson of university council at a time when universities in Kenya were transiting from extreme government administrative control to a greater degree of operational autonomy. Readers will find in this work thought-provoking insights on how leaders of higher education institutions in Kenya have had to balance between demands of the political system and the need to safeguard academic traditions in the everyday management of the institutions.